Spherical particles of phenolic resin treated with iron oxide - dos Santos, Francisco J. [UNESP]; Jafelicci, Miguel [UNESP]; dos-Santos, Claudio G.; de Souza, Rosangela A.; Pasa, Vanya M. D. (Springer, 2008)
This paper describes the preparation and characterization of phenolic resins' thermospheres covered by a magnetic phase of iron oxide. The thermospheres were prepared by allowing phenol and formaldehyde to react under dispersion polymerization conditions and the iron oxide phase was incorporated in situ onto the phenolic resin particles by adding concentrated NH3 to FeCl2 in DMSO. This reaction was conducted at 70 degrees C under nitrogen atmosphere in a controlled temperature vessel, and the modified resin was isolated and dried in vacuo. Both pure and modified resins were characterized by DRX, TG- DTA, and MEV/ EDX. The modified particles were attracted by a magnetic field, indicating the fixation of magnetic iron oxide. No diffraction peaks were observed in DRX analysis; thermal analysis ( DTA) of both pure and modified resins presented exothermic events between 300 and 680 degrees C, and 300 and 570 degrees C, respectively, indicating the microstructure of the resin was modified after the treatment. Thermogravimetric analysis ( TGA) of the pure resin registered a 2.0% residue, compared to 8.0% for the modified resin. These residues correspond to about 7.0% of fixed iron oxide. MEV/ EDX analyses confirm the modification of the resins by the process of fixing iron oxide.